Ancient West & East. (Brill, 2004)
' This new journal from Brill makes many important promises to all scholars interested in the cultures of the ancient Mediterranean and the Near East and the interactions between them. ... By opening a regular avenue for cooperation and conversation among scholars from many disciplines and countries, AWE has a real potential for fulfilling the promises it makes. '// BMCR, 2003.